Anemia and Prognosis in Patients with Acute Venous Thromboembolism - Hofmann, Elena; Stalder, Odile; Méan, Marie; Rodondi, Nicolas; Tritschler, Tobias; Righini, Marc; Aujesky, Drahomir (Thrombosis and Haemostasis, 2025)
Studies found an association between anemia and overall mortality and major bleeding (MB) in patients with acute venous thromboembolism (VTE), but whether anemia is causally related to death, bleeding, or recurrent VTE is uncertain.To explore the association between anemia at baseline and short-/long-term clinical outcomes in a prospective cohort of 928 patients with acute VTE.We defined anemia as a hemoglobin <13 g/dL for men/< 12 g/dL for women. The primary outcome was overall mortality, secondary outcomes were MB and recurrent VTE at 3 months (short term) and over the entire follow-up (long term). An independent committee determined the cause of death. We examined the association between anemia and clinical outcomes using multivariable regression, adjusting for confounders, periods of anticoagulation, and the competing risk of death if appropriate.Overall, 42% of patients had anemia. After a median follow-up of 30 months, 21.4% died, 13.8% experienced MB, and 12.4% had recurrent VTE. Anemia was associated with long-term overall mortality (adjusted HR 1.46, 95%CI 1.06–2.02) but not with short-term mortality, MB, or recurrent VTE. Per 1 g/dL increase in hemoglobin, long-term mortality risk decreased by 8%. Anemic patients were more likely to die from left ventricular failure than non-anemic patients (9.8% versus 1.3%).Anemic patients with VTE carried a higher long-term mortality risk than those without anemia, possibly due to an excess in mortality from left ventricular failure. The lack of an independent relationship between anemia and bleeding indicated that anemia might have confounding rather than causal effects.
Keywords: anemia; venous thromboembolism; prognosis; anticoagulation